Receptor-Interacting Protein Kinase 3 Inhibition Prevents Cadmium-Mediated Macrophage Polarization and Subsequent Atherosclerosis via Maintaining Mitochondrial Homeostasis - Zhang, Jiexin; Feng, Weijing; Li, Minghui; Chen, Peier; Ning, Xiaodong; Ou, Caiwen; Chen, Minsheng (Frontiers in Cardiovascular Medicine, 2021)
Chronic cadmium (Cd) exposure contributes to the progression of cardiovascular disease (CVD), especially atherosclerosis (AS), but the underlying mechanism is unclear. Since mitochondrial homeostasis is emerging as a core player in the development of CVD, it might serve as a potential mechanism linking Cd exposure and AS. Here, we aim to investigate the Cd-mediated AS through macrophage polarization and find out the mechanism of Cd-caused mitochondrial homeostasis imbalance. In vitro, flow cytometry shows that Cd exposure promotes M1-type polarization of macrophages, manifesting as the increasing expressions of NF-kB and NLRP3. Mitochondrial homeostasis tests reveal that the decreasing mitochondrial membrane potential and mitophage, increasing superoxide (mROS) and mitochondrial fission are involved in Cd-induced macrophage polarization. The up-regulated expressions of RIPK3 and p-MLKL are observed. And knocking out RIPK3 with decreasing expression of p-MLKL followed improves mitochondrial homeostasis imbalance which effectively reverses macrophage polarization. In vivo, oil red O staining shows higher blood Cd significantly aggravates AS. Besides, M1-type polarization of macrophages and mitochondrial homeostasis imbalance are observed in mouse aortic roots through immunofluorescence and western blot. And knocking out RIPK3 restores the changes above. Finally, the administered NAC or Mdivi-1, which decreases mROS or mitochondrial fission, inhibits the expressions of RIPK3 and p-MLKL, attenuating AS and macrophage M1-type polarization in Cd-treated group. Consequently, Cd exposure activates RIPK3 pathway and impairs mitochondrial homeostasis, resulting in pro-inflammatory macrophage polarization and subsequent AS. And knocking out RIPK3 provides a potential therapeutic target for Cd-caused macrophage polarization and subsequent AS.